Key witness - Freedman, J. F. (New York : Signet, 1997)
A corporate attorney turns public defender and risks everything to defend a seemingly indefensible young black man charged with seven rape-murders, while the city's racial tensions erupt into violence.
National College of Business and Arts
Keywords: Public defenders -- Fiction; Detective and mystery fiction